Food web analysis of meiobenthos in estuarine seagrss bed. - Vafeiadou, Anna-Maria (2013)
This study examines the resource use and trophic position of nematodes and harpacticoid copepods at a genus/species level in an estuarine food web in Zostera noltii beds and in adjacent sediments, using natural abundances of stable carbon and nitrogen isotopes. Microphytobenthos is among the main resources of most taxa, but seagrass-associated resources also contribute to meiobenthos nutrition, with seagrass detritus being available also in deeper sediments and in unvegetated patches close to seagrass beds. A predominant reliance on chemoautotrophic bacteria was demonstrated for the nematode Terschellingia and the copepod family Cletodidae.